If the gradient of PA is equal to the gradient of PB, then P must lie on the line through A AND B. Otherwise the gradients of PA and PB will be different (you can draw up a diagram to visualise this). So in essense, the locus of P is equation of the line through A and B (as P can lie anywhere on this line such that m(PA) = m(PB))

So find the gradient of AB and use the point gradient-formula to find the eqn of the line

m = (-1-3)/(2-5) = 4/3

therefore, y +1 = 4/3(x-2) [rearrange this and you're done]

## Bookmarks